2004
DOI: 10.1590/s1806-83242004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Current data on the characterization of oral clefts in Brazil

Abstract: ABSTRACT:This study aimed at investigating the current distribution of the several types of clefts among the patients receiving treatment at the Hospital for Rehabilitation of Craniofacial Anomalies (HRAC-USP), Bauru, Brazil, for the first time during the year 2000. A total of 803 unoperated patients with cleft lip and/or palate, with or without additional malformations, with no recognizable syndromes, who came to the HRAC-USP for enrollment for treatment during the year 2000. A predominance of complete cleft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
34
2
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 14 publications
9
34
2
26
Order By: Relevance
“…Recently, in a Brazilian population study, we showed predominance of CLP (52.6%), followed by isolated CL (33.12%) and isolated CP (14.28%) (8). In most published studies, the percentage of subjects with CLP has been higher compared to that of CL or CP alone, including the Brazilian studies (8,12). Some authors studying a population in Sucre, Bolivia, attributed the highest incidence to CL alone (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a Brazilian population study, we showed predominance of CLP (52.6%), followed by isolated CL (33.12%) and isolated CP (14.28%) (8). In most published studies, the percentage of subjects with CLP has been higher compared to that of CL or CP alone, including the Brazilian studies (8,12). Some authors studying a population in Sucre, Bolivia, attributed the highest incidence to CL alone (13).…”
Section: Discussionmentioning
confidence: 99%
“…20 Similar results were observed in a study of the distribution of cleft types in patients attended at a University Hospital in São Paulo. 21 It was observed that 70% of the cases lived under unfavorable socioeconomic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Neste trabalho, observa-se maior predominân-cia das fissuras labiopalatinas no gênero masculino, o que corrobora os achados de outros autores, com exceção das fissuras pós-forame incisivo, que acometem mais o gênero feminino [13][14][15][16] . A fissura transforame incisivo unilateral foi escolhida por permitir a comparação dos dentes com o lado não fissurado.…”
Section: Discussionunclassified
“…A fissura transforame incisivo unilateral foi escolhida por permitir a comparação dos dentes com o lado não fissurado. A maior prevalência desse tipo fissura do lado esquerdo, neste trabalho, é concordante com o resultado de Freitas et al 13 , que encontraram ser esta a de maior frequência no HRAC-USP.…”
Section: Discussionunclassified